Respuesta :
Answer:
(1, 1 )
Step-by-step explanation:
4x - y = 3 ( add y to both sides )
4x = y + 3 ( subtract 3 from both sides )
4x - 3 = y → (1)
7x - 9y = - 2 → (2)
Substitute y = 4x - 3 into (2)
7x - 9(4x - 3) = - 2 ← distribute parenthesis and simplify left side
7x - 36x + 27 = - 2
- 29x + 27 = - 2 ( subtract 27 from both sides )
- 29x = - 29 ( divide both sides by - 29 )
x = 1
Substitute x = 1 into (1)
4(1) - 3 = y
4 - 3 = y
1 = y
solution is (1, 1 )
Answer:(4x - y = 3) * 9
36x - 9y = 27
7x - 9y = -2
29x = 29
x = 1
y = 4*1 - 3
y = 1
Step-by-step explanation:i dont know what kibble is